2004
DOI: 10.1364/josaa.21.001316
|View full text |Cite
|
Sign up to set email alerts
|

Degree of polarization as an objective method of estimating scattering

Abstract: A new method of determining objectively the amount of scattered light in an optical system has been developed. It is based on measuring the degree of polarization of the light in images formed after a double pass through the system. A dual apparatus composed of a modified double-pass imaging polarimeter and a wave-front sensor was used to measure polarization properties and aberrations of the system under test. We studied the accuracy of the procedure in a system that included a lanthanum-modified lead zircona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
(25 reference statements)
0
20
0
Order By: Relevance
“…Previous studies 21,25 concluded that light scattering is the main cause of optical degradation in eyes with cataract; therefore, the measurement of scattering [26][27][28] should be performed when evaluating the optical quality of cataractous eyes. In these cases, analysis of the aberrations seems to be less accurate than the MTF values measured by a double-pass method.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 21,25 concluded that light scattering is the main cause of optical degradation in eyes with cataract; therefore, the measurement of scattering [26][27][28] should be performed when evaluating the optical quality of cataractous eyes. In these cases, analysis of the aberrations seems to be less accurate than the MTF values measured by a double-pass method.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies Bueno et al have proposed the loss of the light polarization as a criterion to evaluate the early eye cataract development [7]. Such criterion is an objective and easy achievable one in the model conditions, however using this way in vivo diagnostics for human eye needs applying a complicated ellipsometric double-pass measuring technique [8].…”
Section: Resultsmentioning
confidence: 99%
“…In camera-based polarimetry methods, polarized light is delivered over the desired ocular region, and the return light from that region is analyzed and imaged by a camera (Figure 2.9). A common configuration is a fixed polarizer in the generator and a rotating retarder and fixed polarizer in the analyzer [20,[31][32][33]. Related comfigurations include a rotating retarder in the generator [34] or use of a liquid crystal variable retarder [35].…”
Section: 4: Experimental Methods For Ocular Polarization Interactionsmentioning
confidence: 99%